PELAKSANAAN PENDEKATAN PEMBELAJARAN MENDALAM DI MATA PELAJARAN IPS PADA SMP DI KECAMATAN KAYEN, KABUPATEN PATI - Salsabila, Ifalda Salsabila Nafa Zahra; Hermanto, Fredy Hermanto (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Social Science (IPS) learning in junior high schools is expected to promote not only content mastery but also deep and contextual understanding. However, in practice, learning remains largely teacher-centered, resulting in limited student engagement. This study aims to analyze the implementation of a deep learning approach in Social Science subjects in junior high schools in Kayen District, Pati Regency. This research employs a qualitative descriptive approach, involving Social Science teachers from three schools as research subjects. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that deep learning has been implemented through planning, implementation, and evaluation stages, but it is not yet optimal. During implementation, contextual learning activities have improved student engagement, although they have not fully promoted higher-order thinking skills. Evaluation practices remain focused on learning outcomes and have not effectively measured critical thinking and knowledge transfer. Therefore, improvements are needed in instructional design, teaching strategies, and assessment instruments that support higher-order thinking skills development.